Improving the Integration of Intermodal Transportation Services in the Poris Plawad Area in Tangerang City - Yusuf, Ferdinan; Priyanto, Sigit; Mulyono, Agus Taufik (Universitas Negeri Yogyakarta, 2025)
The integration of intermodal transportation services is a strategic necessity for improving the quality of urban transportation services. To realize the integration of services, it should be focused on the main transportation nodes in an area, such as Poris Plawad Terminal and Batu Ceper Station in the Poris Plawad Area, Tangerang City. This study aims to evaluate and determine strategies for improving the integration of intermodal transportation services in the Poris Plawad Area. The results of this study are expected to provide consideration for stakeholders to encourage the use of public transportation and realize the successful development of the Poris Plawad Area in the future. The sampling technique used was purposive sampling, with a total sample size of 202 respondents. Respondent data collection was carried out by distributing questionnaires to users of transportation services at Poris Plawad Terminal and Batu Ceper Station, as well as residents who are active within a radius of 800 meters from the terminal and station. This research uses the Importance Performance Analysis (IPA) and Theory of Inventive Problem Solving (TRIZ) methods. The results of the IPA analysis show that there are five service variables that are considered important but low-performing, so they need to be prioritized for improvement, including the provision of pedestrian crossing facilities, the provision of proper sidewalks, disturbance-free pavement quality, and access into and out of the node that is free from traffic conflicts. Recommended solutions based on TRIZ principles include building a sky bridge and closing the south entrance for access into and out of the station; building a sidewalk connected to the node that is built higher than the road surface and uses high-quality materials; placing sidewalk bollards; and permanently closing the station access point that passes through the railway level crossing. These improvements are expected to enhance accessibility, safety, and walkability, encouraging greater public transport use and aligning with the area’s Transit Oriented Development goals.